Newly diagnosed multiple myeloma patients carrying monoallelic deletion of the whole locus of immunoglobulin heavy chain gene have a better prognosis compared to those with t(4;14) and t(14;16). Issue 8 (6th February 2019) - Duek, Adrian; Trakhtenbrot, Luba; Amariglio, Ninette; Benyamini, Noam; Zilbershats, Itay; Ganzel, Chezi; Shevetz, Olga; Leiba, Ronit; Rozic, Gabriela; Nagler, Arnon; Leiba, Merav
Abstract : The current study evaluated the prognostic significance of the monoallelic deletion of the whole locus of the immunoglobulin heavy‐chain (w_del(IGH)) gene compared to translocations t(4;14) and t(14;16) among newly diagnosed multiple myeloma (MM) patients. We retrospectively analyzed clinical (age, gender, and staging) and laboratory data at diagnosis and the overall survival (OS) of 255 newly diagnosed MM patients carrying w_del(IGH) or translocations t(4;14) or t(14;16). Bone marrow samples were examined by morphological and sequential interphase fluorescense in situ hybridization analyses. Among 255 patients, 117 (45.8%) had w_del(IGH), 99 (38.8%) had t(4;14), and 39 (15.3%) had t(14;16). Mean age was 61.6 ± 11.6 years. Groups did not differ significantly in age, gender, or lactate dehydrogenase levels. Patients in the w_del(IGH) group presented more frequently at International Staging System stage I than at stage II/III. Patients in the w_del(IGH) group had significantly fewer additional chromosomal aberrations (1.58) than the other two groups (2.3 and 2.13 in the del(IGH), t(14;16) and t(4;14) groups, respectively, P < 0.0001). Furthermore, the w_del(IGH) group had significantly longer estimated median OS (9.47 years) compared to those with translocations t(14;16) (3.02 years, P = 0.002) or t(4;14) (4.18 years, P = 0.001), respectively. These findings suggest a potential prognostic significance of monoallelic deletion of IGH among these patients. Additional studies are needed to better understand the nature and mechanism of this prognostic factor.